Human Mesenchymal Stem Cell Combined with a New Strontium-Enriched Bioactive Glass: An ex-vivo Model for Bone Regeneration - Devis Bellucci (Materials, 2019)
A 3D cellular model that mimics the potential clinical application of a biomaterial is here applied for the first time to a bioactive glass, in order to assess its biological potential. A recently developed bioactive glass (BGMS10), whose composition contained strontium and magnesium, was produced in the form of granules and fully investigated in terms of biocompatibility in vitro. Apart from standard biological characterization (Simulated Body Fluid (SBF) testing and biocompatibility as per ISO10993), human bone marrow mesenchymal stromal/stem cells (BM-MSCs) were used to investigate the performance of the bioactive glass granules in an innovative 3D cellular model. The results showed that BGMS10 supported human BM-MSCs adhesion, colonization, and bone differentiation. Thus, bioactive glass granules seem to drive osteogenic differentiation and thus look particularly promising for orthopedic applications, bone tissue engineering and regenerative medicine.